Biology, one molecule at a time. - Kapanidis, A; Strick, T (2009)
Single-molecule techniques have moved from being a fascinating curiosity to a highlight of life science research. The single-molecule approach to biology offers distinct advantages over the conventional approach of taking bulk measurements; this additional information content usually comes at the cost of the additional complexity. Popular single-molecule methods include optical and magnetic tweezers, atomic force microscopy, tethered particle motion and single-molecule fluorescence spectroscopy; the complement of these methods offers a wide range of spatial and temporal capabilities. These approaches have been instrumental in addressing important biological questions in diverse areas such as protein-DNA interactions, protein folding and the function(s) of membrane proteins.